The effects of Tualang honey on sperm profile and follicular-stimulating hormone in high cholesterol diet induced animal model - Hasan, Sakiinah; Alias, Mohd Afzal; Abdul Rahim, Roslina; Muhammad, Siti Aeshah @ Naznin; Abdullah, Nor Zamzila; Abdul Razak, Redzuan Nul Hakim (2021)
Introduction: Hypercholesterolaemia is a recognised factor associated with male infertility. However, currently, there is limited therapy available. Tualang honey (TH) is a type of Malaysian polyfloral wild honey produced by the rock bee (Apis dorsata) that has been proven to exert both anti-inflammatory and anti-oxidative effects. This study aimed to determine the effects of TH on the sperm profile and follicular-stimulating hormone (FSH) level of high cholesterol diet (HCD) administered rats. Materials and Methods: Thirty male Sprague Dawley rats were randomly divided into a control group (n=6) fed with the standard diet and HCD group (n=24). The rats in the control group were fed with standard rat pellets while rats in the HCD group were fed with 12% HCD for 16 weeks. At the end of 16 weeks, rats in HCD group were divided into four subgroups (H1, H2, H3, and H4) and continued with 12% HCD in addition to administration of distilled water, 1.2, 2.4, and 3.0 g of honey per kg body weight daily respectively for another 4 weeks. While the rats in the control group continued with commercial rat pellets without honey supplementation for the same duration. At the end of 4 weeks, all rats were sacrificed, and blood specimens were taken for FSH estimation, and the cauda epididymis was collected for sperm analysis. Results: The FSH level and the sperm parameters (sperm concentration, morphology, percentage of total sperm motility,progressive motility, and viability of rats in HCD subgroup H1 were significantly reduced compared to the control (p<0.001). In contrast, all TH supplemented subgroups demonstrated significant improvement in their sperm parameters (p<0.001). The higher the dosage of TH in the HCD subgroup, the greater the improvements in the sperm concentration, morphology, and viability. Although the levels of FSH were increased in all treated HCD groups compared to H1, there was no significant difference in the serum FSH levels between the groups. Conclusion: The Tualang honey supplementation improved the sperm profile in HCD induced animal models.